2022
DOI: 10.1039/d2ce00886f
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun one-dimensional electrocatalysts for boosting electrocatalysis

Abstract: Electrocatalytic reaction plays a crucial role in determining the energy conversion efficiency in advanced technology. However, it is limited by the sluggish reaction kinetics and high energy barrier. These shortcomings...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…112 Electrospinning and hydrogels 113 are also improved techniques for designing porous structures from precursors, starting with highly dispersed nanocarbon bers, unlike synthesis from hard templates. Electrospun nanomaterials with outstanding chemical stability and structural diversity are promising electrocatalysts for the ORR [114][115][116] As shown in Fig. 5a, inside NPCNF-O, b-cyclodextrin acts as a pore inducer and oxygen regulator.…”
Section: Synthesis Of Porous Carbon Materialsmentioning
confidence: 99%
“…112 Electrospinning and hydrogels 113 are also improved techniques for designing porous structures from precursors, starting with highly dispersed nanocarbon bers, unlike synthesis from hard templates. Electrospun nanomaterials with outstanding chemical stability and structural diversity are promising electrocatalysts for the ORR [114][115][116] As shown in Fig. 5a, inside NPCNF-O, b-cyclodextrin acts as a pore inducer and oxygen regulator.…”
Section: Synthesis Of Porous Carbon Materialsmentioning
confidence: 99%
“…In recent years, electrospun one-dimensional (1D) nanomaterials have been considered as efficient electrocatalysts for energy storage and conversion due to their large specic surface area, unique chemical structure, easy adjustment of composition and micromorphology, excellent electron and mass transfer properties, and so on. [26][27][28][29][30][31][32] Kong et al reported the synthesis of 1D bi-carbon nanober catalysts via electrospinning; owing to the large surface area, high selectivity, and unique mass transfer properties, the nanober catalysts show excellent FE for formate (>90%) with a high partial current density of −232.2 mA cm −2 at −1.20 V vs. reversible hydrogen electrode (RHE). 16 Wang et al reported the successful construction of a series of bamboolike La 2 CuO 4 perovskite electrocatalysts with modulated grain boundaries toward CO 2 reduction via electrospinning and subsequent heat treatment, rendering a high FE of 60% towards the production of ethylene.…”
Section: Introductionmentioning
confidence: 99%